Tanggung Jawab Para Pihak Dalam Perjanjian Jual Beli Online Dengan Sistem Cash On Delivery - Haris S B Ong; Marselo Valentino Geovani Pariela (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The COD system, which is the most popular payment method for the public in online buying and selling transactions, but buying and selling online with the COD system is still not understood by the parties, this is because disputes often arise from the parties when making transactions with the COD system.Purposes of the Research: To find out and analyze the form of responsibility of the parties in an online sale and purchase agreement with the COD system. Methods of the Research: The research method uses normative juridical legal methods with primary and secondary legal materials as sources of legal materials, then analyzed qualitatively.Results of the Research: The results show that the form of an online sale and purchase agreement through the COD system between the buyer and seller starts from determining the price, bargaining is carried out before the seller and buyer meet at the agreed location. The Agreements made legally have binding powers such as laws by each party, which creates a legal relationship that results in the emergence of rights and obligations for each party.